Earning response coefficient: the Indonesia stock exchange case / Ambarwati and Eka Sudarmaji - -, Ambarwati; -, Eka Sudarmaji (UiTM Cawangan Johor, 2020)
This research examines the effects of profitability, systematic risk, leverage and earnings persistence on Earnings Response Coefficient (ERC) in companies listed in LQ45 at the Indonesia Stock Exchange (IDX). The objects of this research are companies that are consistently listed in LQ45 in the year of 2015-2017. This study uses panel data regression analysis using the software, Eviews. The empirical results of this research showed that systematic risk and earnings persistence has a significantly negative effect on ERC, leverage has a significantly positive effect on ERC, while profitability does not have an effect on ERC. The results of the research show that the factors of systematic risk, leverage and earnings persistence owned by the company have an effect on investment decisions made by investors.